2021
DOI: 10.7759/cureus.18798
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Get a COVID-19 Vaccine and Its Potential Predictors in Costa Rica: A Cross-Sectional Study

Abstract: Since 2020, the COVID-19 pandemic has had a significant impact on morbidity and mortality around the world. As one of the most successful and cost-effective health interventions for preventing infectious diseases, immunization against SARS-CoV-2, is at the moment the most effective strategy for controlling the current pandemic. Despite the high vaccine acceptance rates that countries such as Costa Rica have shown in the past, the public acceptance of the COVID-19 vaccine is still uncertain. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Although some evidence shows that past events may have eroded trust in the vaccines [8] , the respondents in this study present a high commitment to vaccination campaigns. Our samples present a willingness to be vaccinated similar to the acceptance rate in CH (90.6 %) and CR (86.1 %) found by García and Cerda [20] and Guzmán et al [22] , respectively. However, our acceptance rate is higher than the one found by Solís Arce et al [55] in CO (75 %).…”
Section: Discussionsupporting
confidence: 86%
“…Although some evidence shows that past events may have eroded trust in the vaccines [8] , the respondents in this study present a high commitment to vaccination campaigns. Our samples present a willingness to be vaccinated similar to the acceptance rate in CH (90.6 %) and CR (86.1 %) found by García and Cerda [20] and Guzmán et al [22] , respectively. However, our acceptance rate is higher than the one found by Solís Arce et al [55] in CO (75 %).…”
Section: Discussionsupporting
confidence: 86%
“…Being female was significantly and positively associated with WTR (AOR = 3.45), which is supported by a single study conducted in Ethiopia. 14 Oppositely, findings of studies done in Addis Ababa, 34 Costa Rica, 35 Saudi Arabia, 33 US, 3 Turkey, 19 Survey across countries, 36 and a scoping review 30 indicated males were more likely to show their WTR vaccines if it is available to them. Although it is challenging to scientifically explain this variation, one possible explanation is that women in Ethiopia are more connected to their children and family.…”
Section: Discussionmentioning
confidence: 99%
“…Costa Rica and Colombia, can perhaps be explained by the strength of their vaccination campaigns and receiving vaccine supplies earlier than many other countries [18,19]. Moreover, primary evidence suggests that the potential for the acceptance of Covid-19 vaccines in these countries was particularly high and probably had roots in their longstanding belief in immunization programmes [20,21] that could go beyond the public's confidence in present government. An imbedded belief in immunization programmes has also been reported as a contributor in the success of vaccination campaign in Portugal [22] and its relative failure in the US [23,24].…”
Section: Discussionmentioning
confidence: 99%